Corrigendum: The Sub-Regional Functional Organization of Neocortical Irritative Epileptic Networks in Pediatric Epilepsy - Janca, Radek; Krsek, Pavel; Jezdik, Petr; Cmejla, Roman; Tomasek, Martin; Komarek, Vladimir; Marusic, Petr; Jiruska, Premysl (Frontiers in neurology, 2019)
[This corrects the article DOI: 10.3389/fneur.2018.00184.].
Keywords: epilepsy surgery; interictal epileptiform discharges; propagation; neocortical epilepsy; brain networks; irritative zone